HASIL BELAJAR SISWA PADA MATERI PROTISTA AKIBAT PENERAPAN MODEL LEARNING CYCLE (Journal of Biology Education, 2012)
This research aimed to describe the student’s learning achievements onProtista at SMA Negeri 12 Semarang after the learning cycle models. Pre-experimental research with pretest and posttest group design was implemented in class X-8 and-9. The main data, the students’ learning achievements wererecorded by using the test and non test methods. The supporting data,consisted of student’s activities and teacher’s performances were collectedfrom the researcher’s observation, and student’s responses were collected byquestionnaires. The data were analyzed by N-gain test. The results showed that student’s learning achievements were increased from pretest to posttest with medium N-gain and ? 85% students were successfully passed; 90,73%students were active; and 81,75% students  indicated  positive responses to the learning implemented. The conclusion of this research was that learning cycle model was effective to be used to improve student’s learning achievements on Protista material at SMA Negeri 12 Semarang.   Penelitian ini bertujuan untuk mendeskripsikan hasil belajar siswa SMA Negeri 12 Semarang pada materi protista akibat penerapan model pembelajaran learning cycle. Penelitian pre-experimental design dengan pretest and posttest group design telah dilaksanakan pada kelas X-8 dan X-9. Data utama berupa data hasil belajar yang diperoleh dengan teknik tes dan non tes. Data pendukung terdiri dari data aktivitas siswa dan kinerja guru yang diperoleh dengan metode observasi, serta tanggapan siswa yang diperoleh dengan metode angket. Data dianalisis dengan uji N-gain. Hasil penelitian menunjukkan bahwa hasil belajar siswa mengalami peningkatan pretest ke posttest dengan N-gain sedang dan ?85% siswa tuntas; 90,73% siswa aktif dalam kegiatan  pembelajaran; kinerja guru telah mencapai kriteria baik;  serta 81,75% siswa memberi respon positif terhadap kegiatan pembelajaran yang telah dilaksanakan. Simpulan penelitian ini adalah pembelajaran dengan model learning cycle berakibat baik terhadap hasil belajar siswa pada materi protista di SMA Negeri 12 Semarang.